2008
DOI: 10.1002/per.689
|View full text |Cite
|
Sign up to set email alerts
|

A study of personality in children aged 8–12 years: Comparing self‐ and parents' ratings

Abstract: This cross‐sectional study was designed to investigate personality in children aged 8–12 years. Children's self‐perceptions were compared to parent's ratings. Parents of 506 children completed the Hierarchical Personality Inventory for Children (HiPIC) and children completed a selection of 38 questions from the HiPIC. Results showed that children aged 11–12 years present higher structural congruence, higher reliabilities and higher mean correlation with parents' description than children aged 8–9 years. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
(68 reference statements)
6
14
0
2
Order By: Relevance
“…Although structural validity was verified for both younger and older children, only fifth graders provided self-ratings that displayed an octant scale structure reflecting an ideal circumplex. Moreover, self/peer convergence levels were significant for fourth-and fifth-grade children, but not for younger children, in agreement with Quartier and Rossier (2008). In brief, fourth and fifth graders successfully passed the criteria of structural validity, internal consistency, and self/peer coherence, whereas third graders were less fully convincing.…”
Section: Discussionsupporting
confidence: 76%
“…Although structural validity was verified for both younger and older children, only fifth graders provided self-ratings that displayed an octant scale structure reflecting an ideal circumplex. Moreover, self/peer convergence levels were significant for fourth-and fifth-grade children, but not for younger children, in agreement with Quartier and Rossier (2008). In brief, fourth and fifth graders successfully passed the criteria of structural validity, internal consistency, and self/peer coherence, whereas third graders were less fully convincing.…”
Section: Discussionsupporting
confidence: 76%
“…The children's version of the Hierarchical Personality Inventory for Children or HiPIC (Quartier & Rossier, 2008) was used to evaluate the convergent validation of the BFQ-C. It is a 32-item questionnaire that evaluates the big five dimensions, namely: Extraversion (6 items), Benevolence (9 items), Conscientiousness (7 items), Emotional stability (5 items) and Imagination (5 items).…”
Section: Hipicmentioning
confidence: 99%
“…However this version was designed for a hetero-evaluation by the parents and the teachers. The authors have also derived a version for an auto-evaluation (Quartier & Rossier, 2008) but it only involves 32 items. In this way some dimensions like imagination or emotional stability are only evaluated from 5 items.…”
Section: Introductionmentioning
confidence: 99%
“…The HiPIC is one of the few inventories specifically intended to assess children's personality according to the FFM, and it is the only French-language tool available with norms for clinical practice. Furthermore, Quartier and Rossier (2008) developed a shortened version specifically designed for self-reports, by selecting items on their ease of understanding and readability for school-aged children. Their validation study (Quartier & Rossier, 2008) indicated that the short form had good correlations with the full-scale version, and factorial analyses confirmed its structural validity.…”
Section: Nonlinear Predictions Frequently Stem From Whatmentioning
confidence: 99%
“…There are several possible explanations for these respondent-based (i.e., parent vs. child) divergences. For a start, children's perceptual acuity may depend on the maturation of their self-awareness and their ability to compare themselves with others (Quartier & Rossier, 2008). This would explain why parents and children's assessments tend to converge with age.…”
mentioning
confidence: 99%